A Study To Assess The Effectiveness Of Structured Teaching Programme On Knowledge And Attitude Regarding Immunization Among The Mothers Of Under Five Children In Kurubarapalli - V, Archana; Rajalakshmi, Rajalakshmi (Journal of Neonatal Surgery, 2025)
Background: Immunization is a cornerstone of public health, playing a critical role in avoidance of infectious diseases that disproportionately affect children under the age of five. A study to assess efficacy of structured teaching programmes on attitude and knowledge regarding Immunization between mothers of under five children in Kurubarapalli. Methodology: Research approach was utilized in quasi experimental one group pre-test and post-test design. Target populations for study were selected from Kurubarapalli in Pulliyencheri village. This population was selected by purposive sampling technique. Total samples under study was 30 under five mothers. Data was gathered by organized knowledge questionnaire, which was designated as a study to evaluate effectiveness of structured teaching programme on knowledge and attitude regarding immunization among mothers of under five children. Results were described by utilizing descriptive and inferential statistics. Results: Mean knowledge score exhibited a notable increase from 8.96 (37.33%) in pre-test to 21.73 (90.54%) in post-test, while attitude score rose from 28.9 (41.29%) to 54.03 (77.19%). The statistical significance of these improvements was confirmed through paired t-tests, with t-values of 13.401 for knowledge and 14.21 for attitude, indicating a robust effect of the intervention. Level. Conclusion: Study deduced that a organized teaching programme was effective among mothers of under-children regarding immunization. Stated research hypothesis was accepted.